Taxa de gestação e mortalidade embrionária em receptoras de embriões produzidos in vitro, após sincronização do estro com diferentes protocolos hormonais - Leandro de Araujo Silva (2010)
This study aimed to evaluate the influence of different factors on selection of recipients, pregnancy rates and embryonic mortality following transfer of in vitro produced embryos. It was evaluated 3,507 embryo transfers for recipients displaying natural or synchronized estrus using PGF or progesterone releasing intravaginal devices. Also, it was evaluated the stage of embryonic development, the synchronization between embryo stage and day of estrus of the recipient and the seasons of the year. The rate of selected recipients differed among treatments (p<0.05), 80.6%, 88.6% and 70.9% for natural, PGF and progesterone induced estrus, respectively. The pregnancy rates at the day 60 after transfer did not differ (P>0.05) among treatments: 42.0%, 45.6% and 42.7%, respectively. The pregnancy rates differ (P<0.05) among embryonic development stage, 32.7% for blastocyst, 44.0% for expanded blastocyst and 50.1% for hatched blastocyst. The synchronization between embryo and recipient did not influence pregnancy rates (37.4%, 45.1%, 47.0%, 42.7%, 33.8% for recipients at days 6, 7, 8, 9 and 10 post-estrus, respectively. The season of the year influenced (P<0.05) pregnancy rates (42.0% for summer and 44.6% for winter time, respectively). The average of embryo loss was of 6.4% and did not differ between the analyzed variables.